Internalisasi Nilai-Nilai Religius pada Siswa Kelas V SDN Rantau Jaya Kecamatan Karang Jaya Musi Rawas Utara - Imam Tohari (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
This study describes the religious values that are internalized in the learning of Islamic Religious Education in fifth grade students of Rantau Jaya Elementary School, Karang Jaya District, Musi Rawas North Regency. In this study using field research (field research) with a descriptive approach. The results of the study found that the internalized religious values in the learning of Islamic Religious Education in class V Rantau Jaya Elementary School, Karang Jaya District, Musi Rawas North Regency, namely the value of devotion, the value of student courtesy towards teachers, tolerance and harmony among school members. both teachers and students, respect for fellow school members, discipline in terms of dress and time, concern for fellow school members and community members who need it, and moral values for the environment, namely the value of cleanliness in terms of preserving the school environment through an internalization process through exemplary and habituation.